(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2016)
The article provides an overview of the state of the art involved in the research, with the aim of understanding social representations in the development of citizenship skills from the pedagogical practice in basic secondary education at the Alejandro Gutiérrez Calderón Technical Institute in the municipality of Cúcuta. The research was conducted using a qualitative approach, based on the categories of the civic competence standards formulated by the Ministry of National Education: Coexistence and peace, Participation and democratic responsibility, Plurality, identity, and appreciation of differences.